Exploration of Critical Skills For Teachers In Digital Literacy Practices Education Program - Ocha Trisepta Rachmadiani; Clara Novita Anggraini (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
The increasing penetration of the internet and digital devices significantly impacts learning in technological media. Teachers play an important role in improving their competencies through training programs supported by the government. Dompet Dhuafa's Digital Literacy Education Training for Trainers program aims to improve digital literacy among Sekolah Guru Indonesia (SGI) activists. The program includes training in copywriting, learning video creation, the concept of Society 5.0, and future internet professions. The top five participants' work was certified by the Ministry of Law and Human Rights, highlighting a novel approach as few participants developed strong comprehension and critical thinking skills. This research explores the critical thinking ability of the best participants in the digital literacy program, specifically in creating learning videos that obtain intellectual property rights. The method used was phenomenology, in-depth interviews were conducted with five top participants. The findings of this study revealed three main components affecting the implementation of the program: mastery of critical thinking, lack of mastery of critical thinking, and difficulties in improving participants' critical thinking skills. These results underscore the importance of critical thinking in educational training and the challenges in developing this skill among teachers.